A meta-analysis of the effects of multimodal intervention measures on the recovery of postpartum women after cesarean section - Zhao, Zhi-Min; Yang, Jia-Qi; Wang, Gui-Xian; Yu, Xiao-Jing; Feng, Yun (Frontiers in Medicine, 2025)
ObjectThis systematic review and meta-analysis evaluated whether multimodal intervention bundles improve recovery after cesarean section compared with routine care.MethodsFollowing PRISMA 2020, we searched PubMed, Embase, Scopus, Web of Science, and major Chinese databases (CNKI, Wanfang, VIP) from inception to July 2025 without language restrictions. Eligible randomized controlled trials enrolled postpartum women undergoing cesarean section and implemented bundles comprising ≥2 distinct domains (e.g., opioid-sparing analgesia, early mobilization, early oral intake/nutrition or breastfeeding support, structured nursing, psychological education). The primary endpoint was pain intensity at 24 h (VAS); secondary endpoints included pain at other time points, analgesic consumption, time to first ambulation and first flatus, adverse events, length of stay, breastfeeding initiation/time, and maternal psychological recovery. Relative risks were pooled for dichotomous outcomes and mean (or standardized mean) differences for continuous outcomes, using random effects when heterogeneity was substantial.ResultsTwelve RCTs (n = 1,497), all conducted in China, met inclusion. Multimodal care reduced 24 h pain versus routine care (MD − 0.96 on a 0–10 VAS; 95% CI − 1.28 to −0.64; I2 = 97%), shortened time to first ambulation (MD − 4.58 h; 95% CI − 6.32 to −2.84; I2 = 95%) and to first flatus (MD − 2.28 h; 95% CI − 2.57 to −1.98; I2 = 97%), and lowered overall adverse events (RR 0.28; 95% CI 0.19–0.41; I2 = 0%). No significant difference was observed for time to first breastfeeding (MD 1.39 h; 95% CI − 3.86 to 6.64; I2 = 99%; p = 0.60). Risk of bias was generally moderate to high owing to limited blinding; Egger’s test for the primary outcome did not suggest publication bias.ConclusionCollectively, the current evidence suggests that multimodal, ERAS-oriented care pathways may facilitate safer and more rapid early recovery following cesarean section, particularly by enhancing analgesic efficacy, mobilization, and gastrointestinal function. Nevertheless, the marked heterogeneity in bundle composition, implementation intensity, and outcome definitions, together with the single-country evidence base and moderate risk of bias, substantially limits the certainty and generalizability of these findings.